Surveying the COVID-19 pandemic and its implications : urban health, data technology and political economy - Allam, Zaheer (Elsevier, 2020)
"This timely book surveys the COVID-19 from a holistic, high level perspective, examining such topics as Urban health policy responses impact on cities economies, Urban economic impacts of supply chain disruption, The need for coherent short term urban policies that aligns with long term goals, The rise to citizen science initiatives, The role of open data, The need for protocols to support research collaborations, Building larger infectious disease modelling datasets, NS Advanced computing tools for health policy"--